2000
DOI: 10.1007/s004420050991
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elevated CO 2 on the demography of a leaf-sucking mite feeding on bean

Abstract: The effect of elevated CO on the demography of the arachnid species Tetranychus urticae feeding on Phaseolus vulgaris plants was analysed. This class of herbivores (Arachnida) and its feeding guild (cell content feeders) are under-represented in studies of the combined effects of herbivory and CO. The growth of bean was strongly stimulated by elevated CO. The number of leaves on lateral stems and of flowers increased but pod weight decreased. Leaf nitrogen content was 25% lower at elevated CO due to an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Higher fecundity of BPH in the present study ultimately resulted in proliferated BPH population under elevated condition than ambient condition. This has been reported earlier in case of cotton aphid, Aphis gossypii [ 33 ]; grain aphid, S. avenae [ 27 ] and peach aphid, Myzus persicae [ 34 ]; brown planthopper N. lugens [ 21 ] and corn leaf aphid R. maidis [ 30 ] while, decrease in fecundity was observed in case of woolly beech aphid, Phyllaphis fagi [ 35 ] red spider mite, Tetranychus urticae [ 36 ] and pea aphid, Acyrthosiphon pisum [ 37 ].…”
Section: Resultssupporting
confidence: 65%
“…Higher fecundity of BPH in the present study ultimately resulted in proliferated BPH population under elevated condition than ambient condition. This has been reported earlier in case of cotton aphid, Aphis gossypii [ 33 ]; grain aphid, S. avenae [ 27 ] and peach aphid, Myzus persicae [ 34 ]; brown planthopper N. lugens [ 21 ] and corn leaf aphid R. maidis [ 30 ] while, decrease in fecundity was observed in case of woolly beech aphid, Phyllaphis fagi [ 35 ] red spider mite, Tetranychus urticae [ 36 ] and pea aphid, Acyrthosiphon pisum [ 37 ].…”
Section: Resultssupporting
confidence: 65%
“…Most studies that have investigated the effect of elevated CO 2 on leaf thickness have found that it increases (Pritchard et al . 1999), and this may be associated with increased total mesophyll cross‐sectional area (Radaglou & Jarvis 1992), an extra layer of palisade mesophyll (Thomas & Harvey 1983), or an increase in the thickness of the epidermis (Bouteleb Joutei et al . 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Any reduction in host plant quality is likely to reduce herbivore fitness, through changes in fecundity, survivorship or development rates (e.g. Fajer et al ., 1989; Coviella & Trumble, 1999; Stiling et al ., 1999; Agrell et al ., 2000; Boutaleb‐Joutei et al ., 2000). There are also examples where elevated CO 2 increases plant quality for herbivory (Awmack & Harrington, 2000; Goverde et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%